2020
DOI: 10.1093/biomet/asaa010
|View full text |Cite
|
Sign up to set email alerts
|

Path weights in concentration graphs

Abstract: A graphical model provides a compact and efficient representation of the association structure of a multivariate distribution by means of a graph. Relevant features of the distribution are represented by vertices, edges and other higher-order graphical structures, such as cliques or paths. Typically, paths play a central role in these models because they determine the independence relationships among variables. However, while a theory of path coefficients is available in models for directed graphs, little has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Jones and West (2005) considered the measure of association between two variables provided by the covariance and showed that this quantity can be decomposed in terms of additive weights associated with the paths joining the corresponding vertices. Roverato and Castelo (2020) provided an analysis of the properties of the covariance path weights introduced by Jones and West (2005) and showed that inflation factors play a key role in the interpretation of these quantities; see also Castelo (2017, 2018); Peeters et al (2020).…”
Section: Examplementioning
confidence: 99%
See 4 more Smart Citations
“…Jones and West (2005) considered the measure of association between two variables provided by the covariance and showed that this quantity can be decomposed in terms of additive weights associated with the paths joining the corresponding vertices. Roverato and Castelo (2020) provided an analysis of the properties of the covariance path weights introduced by Jones and West (2005) and showed that inflation factors play a key role in the interpretation of these quantities; see also Castelo (2017, 2018); Peeters et al (2020).…”
Section: Examplementioning
confidence: 99%
“…The comparison of paths with different endpoint requires the use of normalized measures of association and, to this aim, Roverato and Castelo (2020) considered the weights obtained for the decomposition of correlation coefficients. Furthermore, they introduced a novel normalized measure of linear association, named the inflated correlation coefficient, and showed that the weights obtained from the decomposition of this quantity satisfy useful properties that, as far as the strength of paths is of concern, make them an appealing alternative to the classical correlation coefficients.…”
Section: Examplementioning
confidence: 99%
See 3 more Smart Citations